NURSES’ AWARENESS AND PERCEPTION OF FOUR SCORE SCALE VERSUS GLASGOW COMA SCALE TOOL USED AMONG INTUBATED PATIENTS - Mara Ross Abrina Yglesias; Emiliano Ian B. Suson II, (The Malaysian Journal of Nursing (MJN), 2023)
Level of consciousness has always been part of the endorsement and/or data in the nurses notes. Commonly used in the practice is still the GCS. It has also been an observation that in different cases, even though the patients are awake, since they are intubated, verbal response is immediately scored as 1 which contributes to a low GCS score that is relative to a bad prognosis. Also, assessment for complex reflexes are left out which can entail a better assessment on LOC. Hence, this study aims to compare the assessment, awareness, and perception of nurses in different levels of expertise assigned in the emergency department on the level of consciousness of intubated patients using the FSS and GCS tools to hasten triage categorization. It utilized a quantitative, descriptive-comparative type of research conducted in a government hospital in Cebu City. Specifically on the areas of Emergency Department and Non- Trauma, where the researcher has easier access to registered nurses who are taking care of intubated patients. The researcher utilized awareness and perception tools and the FSS and GCS where researcher used complete enumeration involving 32 nurses. In light with the findings of this study, this can be utilized through thorough introduction of the FSS by an expert and on how to utilize the tool.